Placental trophoblast debris mediated feto-maternal signalling via small RNA delivery: implications for preeclampsia. Issue 1 (December 2017) - Wei, Jia; Blenkiron, Cherie; Tsai, Peter; James, Joanna; Chen, Qi; Stone, Peter; Chamley, Lawrence
Abstract To profile the small RNA cargo carried by trophoblast debris derived from the placenta during normal and preeclamptic pregnancies and to determine whether trophoblast debris can deliver its small RNAs to endothelial cells with functional consequences. We confirmed that trophoblast debris can deliver its small RNAs contents to recipient endothelial cells during the co-culture. Next generation sequencing was employed to profile the small RNA contents in both normotensive and preeclamptic trophoblast debris. We identified 1278 mature miRNAs and 2646 non-miRNA small RNA fragments contained. Differential expression analysis identified 16 miRNAs (including miR-145), 5 tRNA fragments from 3 different tRNAs, 13 snRNA fragments and 85 rRNA fragments that were present in different levels between preeclamptic and normotensive trophoblast debris. We loaded a miR-145 mimic into normotensive trophoblast debris via transfection of placental explants from which the debris was derived and found the miR-145 loaded debris induced transcriptomic changes in endothelial cells similar to those induced by preeclamptic trophoblast debris. Trophoblast debris deported into maternal circulation can deliver its small RNA contents to maternal cells thereby contributing to feto-maternal communication. Small RNAs that are dysregulated in preeclamptic trophoblast debris might contribute to the endothelial cell activation which is a hallmark of preeclampsia.